Evidência de validade da Escala Parental de Adaptação à Deficiência - EPAD - Londero, Angélica Dotto (2019)
This thesis aims to carry out the preliminary validation of the Parent Adaptation to Deficiency Scale - PADS. Two studies were carried out: validation of content regarding clarity / pertinence, reliability and internal consistency of the PADS and the validation of construction; and the comparison of the re-idealization in the different deficiencies, considering possible influences of socioeconomic, psychosocial and demographic aspects. It is a quantitative approach study that focused on parental adaptation to disability. Six expert judges participated in the content analysis of the PADS. For the criterion validation, the sampling was non-probabilistic and intentional and counted on 361 parents of subjects with disabilities. Her children attended institutions that serve people with disabilities in the municipality of Santa Maria, Agudo and São Pedro, as well as the Speech and Hearing Service of the Federal University of Santa Maria. A medical records consultation was carried out to collect the sociodemographic data of the family and the application of the PADS with biological parents. The effects of the sociodemographic data were also analyzed in relation to the results of the PADS. In the content analysis the judges identified the pertinence and clarity of the proposed items. The results of the factorial analysis indicated that some items of the scale could be suppressed because they were overlapping factors and indicated 12 factors capable of evaluating the parental adaptation to the deficiency, with special relevance to the diagnostic dimension in the differentiation of the observations. In the analysis of sociodemographic data, it was observed that the higher the parents' schooling and income better the conditions for parental adaptation. The gender and marital status of the parents did not present any relevant interference in the parental adjustment process. It was also observed that parents of children with two or more deficiencies had worse results in parental adaptation. As conclusion of the study it is possible to affirm that the PADS is able to measure the parental adaptation and be used in clinical investigations and also in the process of initial evaluation and control of interventions performed with the parents of disabled subjects.